Analisis Perawatan Mesin Cetak Offset Heidelberg dengan Metode Total Productive Maintenance - Yusnia Sinambela (Jurnal Optimalisasi, 2020)
PT. X is a company that is engaged in printing, the high order requires the company to maintain production machines so that consumer orders can be sent according to the specified time. This company is inseparable from the problem of the effectiveness of the printing machine, because this machine is the company's main machine and improper handling and maintenance of the machine will result in losses. Therefore we need effective and efficient steps in machine maintenance to overcome and prevent these problems. This study discusses maintenance performance by taking into account the value of Mean Time Beetwen Failure (MTBF), Mean Time To Repair (MTTR), and machine availability, using data from May 2019 to April 2020 to find out information about the actual state of the maintenance system, whether good or bad. Based on the results of MTBF data processing, it is concluded that the reliability of the machine is not stable, the MTTR graph is stable, which means that the ability (skill) of the maintenance operator is good and the machine availability needs to be improved.